Vivenciando uma experiência amorosa de cuidado com mães e seus recém-nascidos pré-termo - Oliveira, Maria Emilia de (2006)
ABSTRACT - In this work, the author’s experience at the Neonate Intensive Admission Unit of a teaching hospital in Florianópolis- SC narrated. Starting from a dialogue involving meetings, presence, relationships, calls and answers, the author has offered nursing care of which the main focus was love. The employed methodology was based on Paterson and Zderad’s humanistic model, valuing both objective and subjective knowledge, and encompassing 3 stages: intuitive dialogue, scientific dialogue, and intuitive-scientific conjugation. The implemented proposal allowed to know and think out, in conjunction with the mothers, this process lived throughout premature birth where, through a loving care, great value was given to the relation.  KEY– WORDS: pre-term newborn, loving care, dialogue relation.